2017
DOI: 10.1007/s10067-017-3825-0
|View full text |Cite
|
Sign up to set email alerts
|

RABBIT risk score and ICU admission due to infection in patients with rheumatoid arthritis

Abstract: Rheumatoid arthritis (RA) patients are at increased risk of infection. Aim of the present study was to investigate whether RA patients admitted to an intensive care unit (ICU) due to infection have higher Rheumatoid Arthritis Observation of Biologic Therapy (RABBIT) risk scores compared to control RA patients. Seventy-four RA patients (32.4% male) admitted to an ICU due to infection (from January 2002 to December 2013) and 74 frequency-matched control RA patients (16.2% male) were included in this cross-sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 25 publications
2
12
0
1
Order By: Relevance
“…Although the reported HBV-related mortality ranges from 1.9% to 4.0% in Taiwanese patients with RA [33], all three patients with HBV reactivation in our study died of liver failure, suggesting that the prevention of HBV reactivation is important. A previous study proved that the risk factors for the ICU admission of RA patients due to infection included the non-use of csDMARDs, old age, and comorbidity with COPD or CKD [15]. The current study found that the majority of the 30-day mortality group admitted to our ICU due to infection was nonsurvivors.…”
Section: Discussionsupporting
confidence: 58%
See 4 more Smart Citations
“…Although the reported HBV-related mortality ranges from 1.9% to 4.0% in Taiwanese patients with RA [33], all three patients with HBV reactivation in our study died of liver failure, suggesting that the prevention of HBV reactivation is important. A previous study proved that the risk factors for the ICU admission of RA patients due to infection included the non-use of csDMARDs, old age, and comorbidity with COPD or CKD [15]. The current study found that the majority of the 30-day mortality group admitted to our ICU due to infection was nonsurvivors.…”
Section: Discussionsupporting
confidence: 58%
“…The current study found that the majority of the 30-day mortality group admitted to our ICU due to infection was nonsurvivors. Immunosuppressive treatments, including bDMARDs, csDMARDs, and glucocorticoids, are reportedly associated with infection [15,[34][35][36][37][38][39], whereas we found that the use of csDMARDs reduced the risk of mortality after ICU admission using the multivariate Cox proportional hazards model. Additionally, despite the lack of a signi cant difference in dose-related risk of glucocorticoids in the multivariate analysis, a higher glucocorticoid dose appeared to be associated with an increased risk of mortality.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations